Gold Savings Products at PT. Pegadaian (PERSERO) Parepare Area (Islamic Economic Analysis) - Ilham Putra Usmayani (Al-Kharaj: Journal of Islamic Economic and Business, 2022)
The purpose of this research is to explain how the process of marketing gold savings products at PT. Pegadaian, then what is the process of the mechanism and terms of the gold savings product contract and how is the Islamic economic perception of gold savings products at PT. Pegadaian Persero in Parepare area. The results of research on gold savings products at PT. Pegadaian (Persero) Parepare Area shows that the Marketing Strategy carried out by PT. Pegadaian Persero in the Parepare area with product, price, location and marketing strategies by way of outreach and dissemination via whatsapp online. Then the service process for the Gold Savings product carried out by PT Pegadaian (Persero) is that the customer comes to the nearest pawnshop with several predetermined requirements such as submitting identification, filling out the application form provided, paying the price of the gold bar ordered (cash), paying a down payment ordered gold bars (installments), and signed the agreed transaction contract. to both sides. And gold will be received by customers after paying off installments or other administration.